Frequency of Abnormal EEG Findings in Children from 1 Month to 16 Years of Age Presenting with Epilepsy to Shifa International Hospital Islamabad - Rahman Ullah, Inayat Ullah, Zahir Said (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The objective of this study was to determine frequency of abnormal EEG findings in children from 1 month to 16 years of age presenting with epilepsy to Shifa International Hospital Islamabad. Study Design: It was a cross-sectional study. Setting: Research was conducted at Department of Pediatric Medicine, Shifa International Hospital Islamabad Duration: Duration of study was 6 months from 31st May 2018 to 30th November 2018. Material and Methods: This study involved 217 children of both genders aged between 1 month to 16 years diagnosed of epilepsy who were evaluated by EEG which was labeled abnormal if the wave frequency was 7 MHz or less. A written informed consent was obtained from parents of each patient. Results: The mean age of the children was 7.3±4.4 years. Majority (n=106, 48.8%) of the children were aged 5 years and under followed by 57 (26.3%) children aged between 6-10 years and 54 (24.9%) children aged between 11-16 years. There were 131 (60.4%) male and 86 (39.6%) female children in the study group with a male to female ratio of 1.5:1. Generalized seizures were most frequent type of seizures and were observed in 173 (79.7%) children followed by partial (10.6%), absence (7.4%) and unprovoked (2.3%) seizures. The duration of epilepsy ranged from 1 to 24 months with a mean of 10.8±6.5 months. Abnormal EEG was noted in 170 (78.3%) children with epilepsy. There was no statistically significant difference in the frequency of abnormal EEG across various subgroups based on child’s age (p-value=0.989), gender (p-value=0.900) and duration (p-value=0.958) and type of epilepsy (p-value=0.992). Conclusion: Abnormal EEG was observed in a substantial proportion of children with epilepsy which advocates preferred use of EEG in the diagnostic evaluation of such children owing to its non-invasive nature, low cost and widespread availability. Keywords: Epilepsy, Seizures, Electroencephalography